Kaidah al-Kitābah ka al-Khiṭāb dan Penerapannya dalam Fikih Muamalah - Askar Patahuddin; Jujuri Perdamaian Dunia; Fatimah Mursyid (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to determine the position of the rules of al-Kitᾱbah Ka al-Khiṭᾱb in fiqh muamalah, and to determine the application of the rules of al-Kitbah Ka al-Khib in fiqh muamalah. This study uses a qualitative literature method with deductive data analysis. The research results found are as follows; First; The position of the Rule of Al-Kitābah Ka al-Khiṭāb in Islamic fiqh is the same as the expression/speech. This means that written expressions are the same as verbal expressions, while what is meant in the speech in this discussion is an expression or delivery or something that is conveyed. As well as verbal expression, it is the same as written expression as it is said: